Innovative Imaging Technique for Visualization of Vascularization and Established Methods for Detection of Musculoskeletal Inflammation in Psoriasis Patients - Köhm, Michaela; Zerweck, Lukas; Ngyuen, Phuong-Ha; Burkhardt, Harald; Behrens, Frank (Frontiers in Medicine, 2020)
Psoriasis (PsO) is one of the common chronic inflammatory skin diseases. Approximately 3% of the European Caucasian population is affected. Psoriatic arthritis (PsA) is a chronic immune-mediated disease associated with Psoriasis characterized by distinct musculoskeletal inflammation. Due to its heterogeneous clinical manifestations (e.g. oligo-or polyarthritis, enthesitis, dactylitis, and axial inflammation), early diagnosis of PsA is often difficult and delayed. Approximately 30% of Psoriasis (PsO) patients will develop PsA. The responsible triggers for the transition from PsO only to PsA are currently unclear and the impact of different factors (e.g. genetic, environmental) on disease development are currently discussed. There is a high medical need, recently unmet, to specifically detect those patients with an increased risk for development of clinical evident PsA early to initiate sufficient treatment to inhibit disease progression and avoid structural damage and loss of function or even intercept disease development. Increased neoangiogenesis and enthesial inflammation are hypothesized to be early pathological findings in PsO patients with PsA-development. Different disease states describe the transition from PsO to PsA. Two of those phases are of value for early detection of PsA at-risk patients to prevent later development of PsA as changes in biomarker profiles are detectable: the subclinical phase (soluble and imaging biomarkers detectable, no clinical symptoms) and the prodromal phase (imaging biomarkers detectable, unspecific musculoskeletal symptoms such as arthralgia and fatigue). To target the unmet need for early detection of this risk-population and to identify the subgroup of patients who will transit from PsO to PsA, imaging plays an important role in characterizes patients precisely. Imaging techniques such as Ultrasound (US), magnetic resonance imaging (MRI) and computer tomography (CT) are advanced techniques to detect sensitively inflammatory changes or changes in bone structure. With the use of these techniques, anatomic structures involved in inflammatory processes can be identified. These techniques are complemented by Fluorescence-optical imaging as a sensitive method for detection of changes in vascularization, especially in longitudinal measures. Moreover, high-resolution peripheral quantitative CT (HR-pQCT) and dynamic contrast-enhanced MRI (DCE-MRI) may give the advantage to identify PsA-related early characteristics in PsO patients reflecting transition phases of the disease.